Quality of Academic Services: A Phenomenological Study at the Bureau of Academic and Student Affairs - Munari Munari; Mohamad Irfan Mufti; Abd. Hakim; Muh. Zainuddin Badollahi; Telly Hetty Isje Kondoj (Journal La Edusci, 2025)
This study investigates the quality of academic services at the Bureau of Academic, Student Affairs, and Planning (BAKP) of Tadulako University in Palu. The research uses a qualitative phenomenological approach to explore how academic services are delivered and perceived by students, focusing on five key dimensions: reliability, assurance, physical evidence (tangibles), empathy, and responsiveness. Data were collected through interviews, observations, and documentation from both students and administrative staff. The findings reveal a range of issues that hinder optimal service delivery, including long waiting times, lack of punctuality, inadequate infrastructure, insufficient responsiveness, and undertrained personnel. Students often face delays and miscommunications due to bureaucratic inefficiencies and limited access to information. Moreover, the physical environment, such as cramped waiting areas and poor air conditioning, contributes to user dissatisfaction. Although Standard Operating Procedures (SOPs) are in place, they are not consistently implemented or publicly displayed, further complicating the service process. Officers acknowledge constraints such as understaffing and technical challenges, including frequent network disruptions. Despite efforts to improve services via online platforms, many processes still require manual handling, reducing efficiency and service satisfaction. The study concludes that academic service quality at BAKP requires strategic improvements in human resources, infrastructure, and digital integration to meet students’ expectations and support the university’s academic reputation.